2007
DOI: 10.1021/bm0703362
|View full text |Cite
|
Sign up to set email alerts
|

A New Class of Bioactive and Biodegradable Soybean-Based Bone Fillers

Abstract: The reconstruction of large bone defects in periodontal, maxillofacial, and orthopedic surgery relies on the implantation of biomaterials able to support the growth of new tissue. None of the materials currently available is able to combine all the properties required, which are (i) easy handling, (ii) biodegradation, (iii) low immunogenicity, and more importantly, (iv) induction of tissue regeneration. A new class of biodegradable biomaterials has been obtained by simple thermosetting of defatted soybean curd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 37 publications
2
62
0
1
Order By: Relevance
“…Consequently, it was optimal for placing the scaffolds somewhere between cortical and cancellous bones that create a porous environment with 3-12% and 50-90% porosity, respectively 20 . The scaffold attained a minimal flexural strength of 5 MPa, which was comparable to the strength of cancellous bone (2-10 MPa) 21 . The modulus at 50% porosity (3 GPa) showed a 3-fold increment when changing the sintered temperature from 1050 to 1250°C (Table 1).…”
Section: Discussionmentioning
confidence: 84%
“…Consequently, it was optimal for placing the scaffolds somewhere between cortical and cancellous bones that create a porous environment with 3-12% and 50-90% porosity, respectively 20 . The scaffold attained a minimal flexural strength of 5 MPa, which was comparable to the strength of cancellous bone (2-10 MPa) 21 . The modulus at 50% porosity (3 GPa) showed a 3-fold increment when changing the sintered temperature from 1050 to 1250°C (Table 1).…”
Section: Discussionmentioning
confidence: 84%
“…22,23) Soybean extracts are applied as bone fillers and regenerative materials. 24,25) Safflower seeds are commonly used as a natural remedy to treat bone fractures in traditional Korean medicine, and have recently been used in regenerative applications. 26,27) Other data on safflower seeds include application to the treatment of periodontal 1-wall intrabony defects, 28) and in the prevention of bone resorption caused by estrogen deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Santin and colleagues reported as soybean-based biomaterial granules reduced the activity of monocytes/macrophages and osteoclasts, whereas osteoblast differentiation was induced in vitro [79]. An in vivo study on rabbit found that the implantation of soybean-based granules, after 8 weeks, produced bone repair with different features from those obtained by healing in a non-treated defect [17].…”
Section: Glycine Max Lmentioning
confidence: 99%